2004
DOI: 10.1016/j.tet.2004.09.099
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinium N-2′-pyridylaminide: synthesis of 3-aryl-2-aminopyridines through an intramolecular radical process

Abstract: Abstract-Tris(trimethylsilyl)silane (TTMSS) and azobisisobutironitrile (AIBN) promote the intramolecular heteroarylation of arenesulfonamides with pyridyl radicals under thermal conditions. The arenesulfonamides are easily prepared from pyridinium N-2 0 -pyridylaminide. The heteroarylation process involves pyridyl radical cyclization and ipso substitution. q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nitrene insertion into C−H bonds catalyzed by transition metal complexes is an attractive methodology for the construction of C−N bonds and many interesting organic molecules. Such reactions could play a key role in the preparation of many natural products and pharmacologically active compounds …”
mentioning
confidence: 99%
“…Nitrene insertion into C−H bonds catalyzed by transition metal complexes is an attractive methodology for the construction of C−N bonds and many interesting organic molecules. Such reactions could play a key role in the preparation of many natural products and pharmacologically active compounds …”
mentioning
confidence: 99%
“…This nitrogen in turn induces a partial negative charge on the pyridinium ring, thus reducing its electron-poor character. Taking into account these premises and the previously reported work on the synthesis and reactivity of N -acylaminides, , additional experiments were carried out on the N -acyl salts 17 − 20 . Acylation on the N -exocyclic nitrogen could partially neutralize its electron-donating effect on both the pyridinium and 2-aminopyridine rings.…”
Section: Resultsmentioning
confidence: 99%
“…Pyridinium N -(3′,5′-dibromopyrid-2′-yl)­aminides (e.g., 173a ) have been employed as building blocks in the synthesis of various azine derivatives. When they possess two C–Br bonds, these compounds are primed to undergo late-stage modifications via cross-coupling reactions. Accordingly, Alvarez-Builla and coworkers observed that upon subjecting these compounds to Suzuki–Miyaura coupling conditions with one equivalent of a boronic acid, substitution occurred exclusively at C3 to afford the monocoupled product ( 174 ) as the major product (Scheme ).…”
Section: Directing Group Controlmentioning
confidence: 99%